2013
DOI: 10.1366/12-06756
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Method for Uranium Determination in Ore Sample by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES)

Abstract: A comparison method for the determination (without sample pre-concentration) of uranium in ore by inductively coupled plasma optical emission spectrometry (ICP-OES) has been performed. The experiments were conducted using three procedures: matrix matching, plasma optimization, and internal standardization for three emission lines of uranium. Three wavelengths of Sm were tested as internal standard for the internal standardization method. The robust conditions were evaluated using applied radiofrequency power, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Zaror et al 13 used HF and HNO 3 to decompose phosphate rocks and marine sediments to determine U by ICP OES. They observed that the U 26 with the exception of the soil sample. When U was measured by monitoring the U(II) 367.007 nm line, the U concentration found in the soil was higher than that certied, regardless of the sample decomposition procedure.…”
Section: Sample Analysismentioning
confidence: 97%
“…Zaror et al 13 used HF and HNO 3 to decompose phosphate rocks and marine sediments to determine U by ICP OES. They observed that the U 26 with the exception of the soil sample. When U was measured by monitoring the U(II) 367.007 nm line, the U concentration found in the soil was higher than that certied, regardless of the sample decomposition procedure.…”
Section: Sample Analysismentioning
confidence: 97%
“…Matrix-matched calibration solutions with high levels of Fe or Mg were required to achieve accurate results. For the ICP-AES measurement of U in uranium ores, 369 the results at three U emission lines were compared using matrix-matched standards, plasma optimisation or an internal standard (Sm) as alternative ways of compensating for matrix interferences. The main factor inuencing precision and accuracy was the U wavelength selected but use of a Sm internal standard improved accuracy at all the lines.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…Therefore, the separation and, consequently, detection of rare-earth fission products are particularly important in the HLW treatment process. There are several methods for analyzing radionuclides. These methods include liquid scintillation counting, molecular absorption spectrometry, atomic absorption spectrometry, inductively coupled plasma mass spectrometry (ICP-MS), inductively coupled plasma optical emission spectrometry (ICP-OES), fluorimetry, , capillary electrophoresis, surface-enhanced Raman spectroscopy, , and voltammetry . Most rare-earth isotopes, such as 144 Ce and 143 Pr, undergo β decay.…”
Section: Introductionmentioning
confidence: 99%